Gender‐specific effects of a phytogenic feed additive on performance, intestinal physiology and morphology in broiler chickens. Issue 4 (30th July 2014) - Humer, E.; Rohrer, E.; Windisch, W.; Wetscherek, W.; Schwarz, C.; Jungbauer, L.; Schedle, K.
Summary To date, most studies published were carried out on broilers of the same sex, and possible gender‐specific effects of phytogenic substances have not been investigated so far. A 3 × 2 factorial study was performed to examine gender‐specific effects of a PFA at two dietary levels (150, 1500 ppm) on growth performance, carcass traits and gastrointestinal attributes in broiler chickens versus an untreated control group. The addition of 150 ppm of the PFA led to a downregulation of trypsinogen mRNA in pancreas compared with the control group (p < 0.05). The number of goblet cells decreased in jejunum compared with the unsupplemented group, whereby this effect was more pronounced in male birds (p < 0.05). Furthermore, higher methylamine contents compared with the control group were measured (p < 0.01). In proximal ileum, female birds, supplemented with 150 ppm PFA, had lower crypt depths than their litters in the 1500 ppm treatment (p < 0.05). In distal ileum, villus height:crypt depth ratio was higher in birds fed the PFA at 150 ppm than in the control group (p < 0.05). The 1500 ppm dosage of the PFA increased jejunal histamine concentration compared with the negative control group (p < 0.05). Jejunal histamine concentration was also affected by the interaction PFA × sex (p < 0.05). Regardless of inclusion level, total amount of biogenic amines and other microbial metabolites in digesta samples was not affected by the PFA. These results demonstrate variable, partially gender‐specific effects of the tested PFA. Although the supplementation of 150 ppm showed little effect on mRNA expression level of selected marker genes for nutrient digestion, beneficial effects on gut morphology were observed. The 10‐fold higher dosage of the PFA did not adversely affect growth performance as well as most investigated parameters compared with the control group.